Born to be wild: utilizing natural microbiota for reliable biomedical research - Bruno, Philipp; Schüler, Thomas; Rosshart, Stephan Patrick (Trends in Immunology, 2025)
Laboratory mice housed under specific pathogen–free (SPF) conditions are the standard model in biomedical research. However, experiments with a particular inbred mouse strain performed in different laboratories often yield inconsistent or conflicting data due to housing-specific variations in the composition and diversity of SPF microbiota. These variations affect immune and nonimmune cell functions, leading to systemic physiological changes. Consequently, microbiota-dependent inconsistencies have raised general doubts regarding the suitability of mice as model organisms. Since stability positively correlates with biological diversity, we postulate that increasing species diversity can improve microbiota stability and mouse physiology, enhancing robustness, reproducibility, and experimental validity. Similar to the generation of inbred mouse strains in the last century, we suggest a worldwide initiative to define a transplantable ‘wild’ microbiota that stably colonizes mice irrespective of housing conditions.
CRIS-Team Scopus Importer:2025-02-17
Keywords: activation threshold; dirty mice; metaorganism; natural microbiota; reproducibility; standardization; translational mouse models; wildlings